Persepsi Mahasiswa terhadap Penggunaan Kahoot pada Mata Kuliah Biologi Umum - Amalia Buntu; Sri Wahyuni; Amran Rede (Jurnal Kreatif Online, 2022)
Kahoot can be an option to meet the demands of the 4.0 era in teaching. The use of this kind of application should not only be limited to fulfilling these demands. The implication of the application for students is also an important thing to study. This study aims to describe student perceptions of the use of Kahoot in learning activities, specifically in online learning. This research was conducted in the odd semester of the 2020/2021 academic year in the General Biology course. This research is descriptive. The data in this study were collected using the help of a questionnaire regarding student perceptions. The study results found that overall, students felt that there was no difficulty in the accessibility of Kahoot, students felt that using Kahoot for quizzes was helpful in General Biology learning, students felt that taking quizzes with Kahoot was easy to implement, and students had a positive attitude towards using Kahoot for the quiz.